Determinación de las variables que forman el salario emocional y diseño de estrategias para potencializarlo. Caso personal administrativo UPS sede Quito - Campus Girón - Lucio Astudillo, Tatiana Elizabeth (2013)
Human talent is the driving force in an organization, so that it becomes an essential requirement, proper maintenance and management in order to maintain a good corporate image both internal and external that favor the admission of qualified personnel and simultaneously ensure that the organization remains within the competitive market. The recognition of performance, good working environment, equity and empathy, teamwork, knowledge and establishment of organizational goals, knowledge of the importance of the work inside the organization, respect, good communication, are some of the variables that increase or decrease the level of emotional salary a collaborator within an organization, depending on the treatment that the administrator give each one of them to manage human talent.